Isotopic ratios in titan's atmosphere from cassini CIRS limb sounding: CO2 at low and midlatitudes - Nixon, C; Jennings, D; Bézard, B; Teanby, N; Achterberg, R; Coustenis, A; Vinatier, S; Irwin, P; Romani, P; Hewagama, T; Flasar, F (Institute of Physics Publishing, 2008)
This Letter reports on a search for infrared emissions of isotopologues of CO2 in the atmosphere of Titan using spectral data recorded by the Cassini Composite Infrared Spectrometer (CIRS). We have made a successful 6.5 σ detection of 13CO2 at a fraction CO 2/13CO2 = 84 ± 17, consistent with measurements of 12C/13C in other species, and also the terrestrial value (89). We also And a probable 3.5 σ detection of C 16O18O at a fraction CO2/ C16O 18O = 173 ± 55, slightly lower than the terrestrial value (253) and consistent with the twofold enhancement in 18O reported previously in CO, or with an intermediate value as suggested by chemistry. These isotopic ratios provide important constraints on models of the formation, evolution, and current processes in Titan's atmosphere. © 2008, The American Astronomical Society, All rights reserved.